The effects of dietary intervention with turmeric on lipid profile and anthropometric indices in overweight/obese women with hyperlipidemia: a randomized controlled clinical trial - Atakan, Ayşegül; Kabaran, Seray; Eren, Fatma Hülyam (Progress in Nutrition, 2022)
Background and Objective: The objective of this trial was to evaluate the effects of turmeric on blood lipids and body weight loss in overweight/obese women with hyperlipidemia. Methods and Study Desing: In this randomized controlled trial, overweight/obese hyperlipidemic women (BMI>25 kg/m2) were randomly divided into 2 groups as turmeric (n=35; 4 g/d) and control (n=35) groups for 8 weeks. The subjects included in the turmeric and control groups adhered to a medical nutrition therapy. Serum lipid profile and anthropometric data were measured at the beginning and again at the end of the study. Results: After 8 weeks of dietary intervention, both turmeric and control groups showed significant decreased in total cholesterol (‑55.66 versus ‑53.06 mg/dl), LDL‑C (‑35.70 versus ‑35.91 mg/dl) and TG (‑44.34 versus ‑42.03 mg/dl), respectively (p<0.01). Body weight (‑5.05 versus ‑4.91 kg), BMI (‑1.88 versus ‑1.84 kg/m2), body fat ratio (‑4.02 versus ‑3.30%) and waist circumference (‑4.70 versus ‑3.74 cm) were also significantly decreased after dietary intervention in both groups, respectively (p<0.001). No significant difference was found in the reductions of total cholesterol, LDL‑C, TG concentrations or in the reductions of body weight, BMI and waist circumference between the turmeric and control groups (p>0.05). Conclusions: Further randomized controlled trials with longer supplementation durations are needed for a stronger assessment of the lipid-modulating properties of turmeric.